Sg- Open Sets in Topological Spaces - Darwesh, H M.; Hessea, N O. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, we introduce a new type of semi-open sets which we call Sg - open sets, and then we study some its basic properties and characterizations, further, we investigate some relationships with some other types of sets.
Keywords: Semiopen sets; gclosed sets; Sgopen sets